The Influence of Country of Origin, Brand Image, and Product Quality on Purchasing Decisions for Cosrx Skincare - Luqy Aizzatul Fakhiroh; Siti Aminah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Skincare has developed rapidly in the last few years, the skincare brands available are very diverse, one of which is Cosrx which comes from South Korea. South Korea is considered a highly innovative country in the beauty and skincare industry, known for its advanced technology and effective product formulations. This research aims to determine the influence of Country of Origin on the decision to purchase Cosrx skincare, the influence of brand image on the decision to purchase Cosrx skincare, and the influence of product quality on the decision to acquire Cosrx skincare. The research method used is quantitative research. The sample in this study used the Likert formula and the results were 90 respondents. The Purposive Sampling method was used for sampling. The data analysis approach uses the PLS (Partial Least Square) program. Based on the research results, country of origin, brand image and product quality all positively and significantly influence consumer purchasing decisions for Cosrx skincare.